The regulation drug approach in Afghanistan and its impact on regional criminal - Ahmad Reza Sadeghi, Mohammad Ali Haji Deh Abadi, (Opción, 2019)
The aim of the study is to investigate the regulation drug approach in Afghanistan and its impact on regional criminal via comparative qualitative research methods. As a result, by the regionalization of criminal policy in the form of transnational interest-based practices, not only the convergence of regional criminal law evolves, but provides the context for the development of regional pluralism. In conclusion, regarding the actions of the ECO countries, what is currently considered to be the framework for cooperation between ECO member countries for organized crimes, especially narcotics, is the mere synchronization approach.